The Accuracy of Confocal Laser Endomicroscopy in Diagnosing Bladder Cancer: A Systematic Review & Meta-Analyses - Hafizar Hafizar; Etriyel MYH (Indonesian Journal of Cancer, 2021)
Background: Multiple advancements of endoscopic technology were designed to enhance the sensitivity and specificity of the diagnostic tools of bladder cancer; thus, we perform a meta-analysis to compare diagnostic performance between confocal laser endomicroscopy (CLE) and biopsy for detecting bladder cancer.Methods: We compared CLE’s accuracy in diagnosing bladder cancer reported by studies obtained from the electronic database MEDLINE, CENTRAL, and CINAHL, from May to June 2020. The pooled effect estimate was calculated employing the DerSimonian and Laird random-effects model. We only included moderate to high-quality studies, which had been assessed by the QUADAS-2 tool.Results: Eight studies were included in this review; five of those were good-quality studies. A total of 519 samples from 345 patients were included in the pooled effect estimate calculation. Pooled sensitivity and specificity of CLE in diagnosing bladder cancer were 90.2% (0.86, 0.93) and 78.1% (0.71, 0.85), respectively. The use of white-light cystoscopy (WLC) before CLE increased its specificity (56.8% versus 84.6%). Pooled sensitivity and specificity of CLE in predicting lowgrade lesion were 73% (0.66, 0.80) dan 83% (0.78, 0.87), respectively. Meanwhile, pooled sensitivity and specificity of CLE in predicting high-grade lesion were 73% (0.66, 0.78) and 79% (0.73, 0.83), respectively.Conclusions: CLE has good accuracy in distinguishing malignant and benign tumors. Grading tumors with this modality is also accurate. The use of probe CLE (pCLE), coupled with WLC, will increase its specificity.